2(n - 1) + 4n = 2(3n - 1)
2n - 2 + 4n = 6n -2
6n - 2 = 6n - 2 (equal)
6n - 6n = 2 - 2
0 = 0
whatever value you put into the place of n, you'll get 0 = 0
Answer:
33.333...% over the base 100% (100% is representing the $5.40)
Step-by-step explanation:
she gets $7.20 from selling the 18 chocolate bars
7.20 divided by 5.40 is 1.3333...
the 1 in 1.3333... represents the base 5.40 and the 0.3333... represents the profit
Answer:
He should buy 4 boxes
Step-by-step explanation:
25 divided by 8 is 3.125, but you want to have enough so the least amount you can buy is 4.
Answer:
y = 2cos5x-9/5sin5x
Step-by-step explanation:
Given the solution to the differential equation y'' + 25y = 0 to be
y = c1 cos(5x) + c2 sin(5x). In order to find the solution to the differential equation given the boundary conditions y(0) = 1, y'(π) = 9, we need to first get the constant c1 and c2 and substitute the values back into the original solution.
According to the boundary condition y(0) = 2, it means when x = 0, y = 2
On substituting;
2 = c1cos(5(0)) + c2sin(5(0))
2 = c1cos0+c2sin0
2 = c1 + 0
c1 = 2
Substituting the other boundary condition y'(π) = 9, to do that we need to first get the first differential of y(x) i.e y'(x). Given
y(x) = c1cos5x + c2sin5x
y'(x) = -5c1sin5x + 5c2cos5x
If y'(π) = 9, this means when x = π, y'(x) = 9
On substituting;
9 = -5c1sin5π + 5c2cos5π
9 = -5c1(0) + 5c2(-1)
9 = 0-5c2
-5c2 = 9
c2 = -9/5
Substituting c1 = 2 and c2 = -9/5 into the solution to the general differential equation
y = c1 cos(5x) + c2 sin(5x) will give
y = 2cos5x-9/5sin5x
The final expression gives the required solution to the differential equation.
Answer:
a = -5
Step-by-step explanation:
6a + 20 = 2a
6a = 2a - 20
4a = - 20
a = -5